2020
DOI: 10.3390/nu12082427
|View full text |Cite
|
Sign up to set email alerts
|

The Absence of Adiponectin Alters Niacin’s Effects on Adipose Tissue Inflammation in Mice

Abstract: Obesity is an immunometabolic disease associated with chronic inflammation and the dysregulation of pro- and anti-inflammatory cytokines. One hallmark of obesity is reduced concentrations of the anti-inflammatory adipokine, adiponectin. Pharmacologic doses of niacin produce multiple metabolic benefits, including attenuating high-fat diet (HFD)-induced adipose tissue inflammation and increasing adiponectin concentrations. To determine if adiponectin mediates the anti-inflammatory effects of niacin, male C57BL/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 71 publications
0
4
0
1
Order By: Relevance
“…In our single-cell analysis, it was observed that ADIPOQ exhibited expression in nearly all cell types, with the exception of granulocytes. ADIPOQ, an anti-in ammatory adipokine [44], has been associated with the risk factors of GDM, which is characterized by chronic lowgrade in ammation [45]. During pregnancy, ADIPOQ levels decrease, and this decrease is further pronounced in individuals with GDM [16].…”
Section: Discussionmentioning
confidence: 99%
“…In our single-cell analysis, it was observed that ADIPOQ exhibited expression in nearly all cell types, with the exception of granulocytes. ADIPOQ, an anti-in ammatory adipokine [44], has been associated with the risk factors of GDM, which is characterized by chronic lowgrade in ammation [45]. During pregnancy, ADIPOQ levels decrease, and this decrease is further pronounced in individuals with GDM [16].…”
Section: Discussionmentioning
confidence: 99%
“…This methylation promoted the stability of TSC2 by interfering with Akt-mediated phosphorylation at T1462. Inhibition of PRMT1 is often considered the target for treating cancer cells 35 . In general, methionine restriction (MR), which reduces the methyl donor for PRMTs, has been well studied as inhibiting tumour development in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in fat cells, niacin suppresses TNF-α-induced release of proinflammatory cytokines and chemokines which may promote accumulation of macrophages and T-cells in atherosclerotic plaques. Thus, niacin may have an impact on atherosclerosis-associated inflammatory processes through its effect on the adipose tissue (Graff et al, 2020).…”
Section: Non-lipoprotein-related Effects Of Niacinmentioning
confidence: 99%